2015
DOI: 10.1177/1468017314568081
|View full text |Cite
|
Sign up to set email alerts
|

Family resilience in families where a parent has a mental illness

Abstract: Summary This study explores the concept of family resilience where a parent has a mental illness. Eleven Australian adults who have grown up in a household with a parent who had a diagnosed mental illness participated in an in-depth interview. The interviews focused on the ways in which these families responded to challenges in everyday life, particularly related to parental mental illness. Findings Families developed resilience through processes such as shared humour or regular family rituals and routines. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
48
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(56 citation statements)
references
References 24 publications
5
48
0
3
Order By: Relevance
“…This is also consistent with research by Distelberg and Taylor () and Power et al. (), who found that higher levels of family resilience were associated with greater use of external resources. Black and Lobo () also describe social support to be a factor challenging to a family's resilience; however, it is increasingly undermined owing to the families’ disconnect from society.…”
Section: Introductionsupporting
confidence: 92%
See 1 more Smart Citation
“…This is also consistent with research by Distelberg and Taylor () and Power et al. (), who found that higher levels of family resilience were associated with greater use of external resources. Black and Lobo () also describe social support to be a factor challenging to a family's resilience; however, it is increasingly undermined owing to the families’ disconnect from society.…”
Section: Introductionsupporting
confidence: 92%
“…In addition, Power et al. () explored the complexities of family resilience processes and they also found that along with family connectedness being integral to family functioning, so was the connection and support found beyond the immediate family; in other words, their perceived social support and economic resources .…”
Section: Introductionmentioning
confidence: 99%
“…It can include a range of family-inclusive practices, including, but not limited to, identifying parental status and the existence of dependent children, referring clients' dependent children to support services, the provision of psycho-education to family members, and the delivery of formal family interventions (Foster et al 2012;Goodyear et al 2015a). In a study of the promotion of family resilience, Power et al (2015) recommended that in addition to psychoeducation, mental health practitioners need to facilitate an open discussion about a parent's mental illness and the impacts on the family, without disempowering or shaming the person with the mental illness. In a study of the promotion of family resilience, Power et al (2015) recommended that in addition to psychoeducation, mental health practitioners need to facilitate an open discussion about a parent's mental illness and the impacts on the family, without disempowering or shaming the person with the mental illness.…”
Section: Introductionmentioning
confidence: 99%
“…Accommodating a diversity of need as well as a resilience-promoting early intervention focus for all family members requires practice that does not rely on one service sector alone Power et al, 2015). A cross-sector approach that recognizes the multiservice system structure potentially involved in addressing the needs of a family is essential (Blanch, Nicholson, & Purcell, 1994;Bromfield, Lamont, Parker, & Horsfall, 2010;McDonald & Rosier, 2011).…”
mentioning
confidence: 99%